Verbal episodes as instrument to analyze the therapeutic relationship (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
To identify variables in the therapeutic process contributes to a better comprehension of client-therapist relationship. The objective of this research are to verify verbal operants that occur in the client-therapist relationship, identify a behavior unit and define the verbal episode in the therapeutic relationship. Two therapeutic sessions were recorded and transcribed defining each verbal episode. The episodes identified as tacts (55 episodes; 90,5%) were controlled by specific stimulus of speaker/client everyday life of which 19 were classified as impure tacts. The low frequency of mands (6; 9,5%) compared to the high frequency of tacts may be related to the consequences displayed by the therapist to the mand responses. The verbal analysis of the speeches permitted a clear control of verbal responses and allowed the therapist a close contact with important variables of the client-therapist relationship, contributing to change the clients behaviors.
Keywords: Verbal Behavior; Client-therapist Relationship; Verbal Episode; Verbal Operants; process research.